2017
DOI: 10.3390/rs10010033
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Mapping from Satellites: An Intercomparison of SMAP, SMOS, FY3B, AMSR2, and ESA CCI over Two Dense Network Regions at Different Spatial Scales

Abstract: Abstract:A good knowledge of the quality of the satellite soil moisture products is of great importance for their application and improvement. This paper examines the performance of eight satellite-based soil moisture products, including the Soil Moisture Active Passive (SMAP) passive Level 3 (L3), the Soil Moisture and Ocean Salinity (SMOS) Centre Aval de Traitement des Données SMOS (CATDS) L3, the Japan Aerospace Exploration Agency (JAXA) Advanced Microwave Scanning Radiometer 2 (AMSR2) L3, the Land Paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 61 publications
12
102
1
Order By: Relevance
“…Launched in January 2015, SMAP provides soil moisture observations at an unprecedented 9-km and approximately 3-d resolution. Daily average soil moisture is observed at a spatial resolution analogous to county-level maize yields 38 and these outperform other remotely sensed soil moisture data products when compared with in situ soil moisture measurements 39,40 . SMAP observes soil moisture to a depth of approximately 5 cm, which we use as the surface boundary forcing of a simple hydrologic model 41 to estimate root-zone soil moisture.…”
Section: Retrospective Yield Predictions Across the Us Midwestmentioning
confidence: 82%
“…Launched in January 2015, SMAP provides soil moisture observations at an unprecedented 9-km and approximately 3-d resolution. Daily average soil moisture is observed at a spatial resolution analogous to county-level maize yields 38 and these outperform other remotely sensed soil moisture data products when compared with in situ soil moisture measurements 39,40 . SMAP observes soil moisture to a depth of approximately 5 cm, which we use as the surface boundary forcing of a simple hydrologic model 41 to estimate root-zone soil moisture.…”
Section: Retrospective Yield Predictions Across the Us Midwestmentioning
confidence: 82%
“…L-band microwave radiometry, a component of synthetic aperture radar systems, has been shown to be a reliable approach to estimate soil moisture via satellite-based remote sensing [223], such as using the ESA's Soil Moisture and Ocean Salinity (SMOS) [224] and NASA's Soil Moisture Active Passive (SMAP) satellites [225,226]. The limitation of the SMOS and SMAP missions, with regard to horticultural application, is their depth of retrieval (up to 5 cm) and spatial resolution (in the order of tens of kilometre) [227][228][229]. As an airborne application, the volumetric soil moisture has been estimated by analysing the SNR of the GNSS interference signal [230,231].…”
Section: Soil Moisturementioning
confidence: 99%
“…The differences in the strength and timing of the statistical relationship for all three data sets suggest that the SMOS data set, which presumably has the highest accuracy since the sensor characteristics were designed specifically to measure soil moisture, is capturing this trend better than the other two data sets. SMOS soil moisture has been shown to have a higher accuracy than ESA-CCI in previous studies [5]. The weaker relationship with the ESA-CCI data set may be due to the statistical rescaling of that data set to the GLDAS model, which may be reducing the dynamic range of the data set, with a bias toward drier soil moisture values (Figure 4, Table 1).…”
Section: Impact Of Data Type On the Relationship Between Soil Moisturmentioning
confidence: 84%
“…These soil moisture data sets have been validated around the world using in situ station networks. Validation results have shown that the volumetric soil moisture derived from L-band frequencies is more accurate than those using higher radiometric frequencies such as X-and C-band, but the temporal trend in soil moisture (i.e., wetting and drying cycles) can be captured reasonably well using all three types of data [4,5]. Satellites are sensitive to the moisture in a thin layer of soil at the surface, limiting their use for monitoring root zone soil moisture most closely associated with agricultural droughts.…”
Section: Introductionmentioning
confidence: 99%